Usefulness of measurement of fibrinogen, D-dimer, D-dimer/fibrinogen ratio, C reactive protein and erythrocyte sedimentation rate to assess the pathophysiology and mechanism of ischaemic stroke. Issue 9 (4th February 2011) - Alvarez-Perez, F J; Castelo-Branco, M; Alvarez-Sabin, J
Abstract : Background: Classification defined in the Trial of Org10172 in Acute Ischaemic Stroke (TOAST) is widely used in trials and practice. Previous studies on pathophysiology suggest a role for endothelial inflammation in atherothrombotic strokes and intracardiac thrombosis in cardioembolic strokes. Data on lacunar and undetermined strokes are limited. The aim of the study was to assess non-specific inflammatory and thrombogenic parameters in patients with ischaemic stroke. Methods: This was a prospective controlled clinical study involving 200 patients with ischaemic stroke and 50 controls. Patients were classified following the TOAST criteria. Plasma levels of fibrinogen, D-dimer, C reactive protein and values for D-dimer/fibrinogen ratio and erythrocyte sedimentation rate were assessed over 48 h after admission. Clinical severity was measured using the National Institutes of Health Stroke Scale and the Oxfordshire Community Stroke Project classification. Patients with severe systemic disorders were excluded. Results: The assessed parameters were significantly higher in patients versus controls. Cardioembolic stroke patients showed increased D-dimer, fibrinogen and D-dimer/fibrinogen ratio. Patients with atherothrombotic stroke showed raised fibrinogen and erythrocyte sedimentation rate. Patients with lacunar and undetermined stroke showed intermediate values of markers. Total anterior cerebral infarction syndrome was related to D-dimer. Discussion: Patients showed analytical modifications during the acute phase of stroke, both related to acute response and mechanism. The results suggest that the biochemical profile may be prothrombotic in patients with cardioembolism and inflammatory in those with atherothrombotic stroke. Patients with lacunar and undetermined stroke showed intermediate profiles. Assessment of the studied parameters is not expensive, widely available and may proportionate information about pathophysiology in stroke patients without severe systemic conditions.